2018
DOI: 10.1186/s12885-018-5126-7
|View full text |Cite
|
Sign up to set email alerts
|

The ASAMET trial: a randomized, phase II, double-blind, placebo-controlled, multicenter, 2 × 2 factorial biomarker study of tertiary prevention with low-dose aspirin and metformin in stage I-III colorectal cancer patients

Abstract: BackgroundEpidemiological studies and cardiovascular prevention trials have shown that low-dose aspirin can reduce colorectal cancer (CRC) incidence and mortality, including inhibition of distant metastases. Metformin has also been associated with decreased colon adenoma recurrence in clinical trials and lower CRC incidence and mortality in epidemiological studies in diabetics. While both drugs have been tested as single agents, their combination has not been tested in cancer prevention trials.Methods/designTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Nonetheless, there were insignificant different in OS and disease free survival (DFS) among the metformin, non-metformin, and non-diabetic patients. Currently, an ongoing randomized, phase II, double-blind, placebo-controlled trial aims to determine the effect of low-dose aspirin and metformin in stage I-III CRC patients since the single use of both drugs exhibited beneficial use in reducing adenoma recurrence and CRC mortality rates [102]. The CRC patients ( n = 160) are divided in four arms; aspirin (100 mg/day), metformin (850 mg/bis in die), aspirin and metformin combination, or placebo for a duration of 12 months.…”
Section: The Clinical Use Of Metformin In Crc Interventionmentioning
confidence: 99%
“…Nonetheless, there were insignificant different in OS and disease free survival (DFS) among the metformin, non-metformin, and non-diabetic patients. Currently, an ongoing randomized, phase II, double-blind, placebo-controlled trial aims to determine the effect of low-dose aspirin and metformin in stage I-III CRC patients since the single use of both drugs exhibited beneficial use in reducing adenoma recurrence and CRC mortality rates [102]. The CRC patients ( n = 160) are divided in four arms; aspirin (100 mg/day), metformin (850 mg/bis in die), aspirin and metformin combination, or placebo for a duration of 12 months.…”
Section: The Clinical Use Of Metformin In Crc Interventionmentioning
confidence: 99%
“…Firstly, it was proposed that aspirin affects the nuclear transport of Slug. Previous studies have demonstrated that aspirin can downregulate the expression of Slug in aggressive K-ras-expressing cancer cells (26,27). A previous study has also implicated aberrant nuclear transport of Snail family member transcription factors in tumor formation (28).…”
Section: Discussionmentioning
confidence: 97%
“…73 In another randomized, Phase II, double-blind, placebocontrolled, multicenter, ASAMET trial, the combination of aspirin and metformin was assessed for their potential synergistic interaction on a set of biomarkers associated with colon carcinogenesis. 74 Here, the patient trial administered metformin at 850 mg BID (twice a day) and aspirin at 100mg QD (once a day) for one year.…”
Section: Discussionmentioning
confidence: 99%